ANALISIS MANAJEMEN KUALITAS DENGAN PENDEKATAN TOTAL QUALITY MANAGEMENT BERBASIS DEMING PRIZE DI ROTTE BAKERY PEKANBARU - Situmorang Mora Kenny; Samsir Samsir; Daulay Nauli Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the quality of management at Rotte BakeryPekanbaru with a Total Quality Management approach based on the DemingPrize. The method used in this research is descriptive quantitative approachmethod. The population in this study were all 18 branches/outlets of Rotte BakeryPekanbaru. In this study, researchers used non-probability sampling with thetechnique taken, namely saturated sampling (census). The number of samples tobe studied is 18 branches/outlets of Rotte Bakery Pekanbaru. The data in thisstudy were analyzed with the Deming Prize. The results of this study indicate thatthe Analysis of Quality Management with a Total Quality Management ApproachBased on the Deming Prize at Rotte Bakery Pekanbaru consists of four indicators,namely from the Deming Prize, namely the State of the Company, WorkProcesses, Management Tools and Outputs Produced. In the company's statevariable which shows that the company has service quality as seen from the stateof the company with an average number of 4.32 in the interval 4.20 - 5.00 with avery good category. In the work process variable which shows that the companyhas service quality as seen from the state of the company with an average numberof 4.31 in the interval 4.20 - 5.00 with a very good category. management toolvariable which shows that the company has service quality as seen from themanagement tool with an average number of 4.02 in the interval 4.20 – 5.00 witha very good category. In the resulting output variable, which shows that thecompany has a service quality that is seen from the output produced with anaverage number of 3.80 is in the interval 4.20 - 5.00 with a very good category.Of the four indicators, the score results are in the very good category, which is inthe range of values from 4.20 to 5.00. Keywords: Quality Management, TQM, Deming Prize.